PERBEDAAN PENGUNGKAPAN CORPORATE SOCIALRESPONSIBILITY DAN NILAI PERUSAHAAN ANTARA PERUSAHAAN DENGAN MANAJEMEN LABA TINGGI DAN RENDAH - Muhamad Yulio Horison; Yeterina W Nugrahanti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2014)
This research aimed to determine whether corporate social responsibility disclosures and the value of the firm in each mining company listed on Indonesia Stock Exchange (BEI) in 2012 differ between firm with high and lower earnings management. The corporate social responsibility disclosures measured using corporate social disclosure index (CSDI) based on Global Reporting Initiative (GRI) reporting standard items which were disclosed in companies annual report while the value of the firm was measured using Tobin’s Q Model. Earnings management was measured by discretionary accruals used in The Khotari et. al. Model (2005). The sample consisted of 36 mining companies listed on BEI in 2012. Data analysis used in this research was Mann-Whitney U Test. The result of this research indicated that there was difference of corporate social responsibility disclosures between firms with high and lower earnings management. While for the value of the firm, there was no difference between firms with high and lower earnings management.